PERAN UNITED NATIONS ASSISTANCE MISSION IN AFGHANISTAN (UNAMA) DALAM MEMBERIKAN PERLINDUNGAN HAK ASASI MANUSIA DI AFGHANISTAN PADA TAHUN 2009-2012 - Fuadi, Ahmad; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research analyzes the role of United Nations Mission (UNAMA) on protecting the human rights in Afghanistan, especially during 2009 until 2012. Afghanistan is well known with its conflicts. Since the departure of Soviet Union in 1989, Afghanistan has fallen into civil wars. Many groups tried to take the seat of government until the Taliban rose. The Taliban became the most powerful group in Afghanistan until its major defeat in 2002 by Anaconda Operation of United States and its allies. UNAMA has been playing a positive role in Afghanistan since its formation in 2002. In realizing its goal to protect human rights staying respected as mandated in the United Nations’ Charter, UNAMA is supported by human rights unit. UNAMA is also supported by other international organizations. UNAMA made four priority areas of work in protecting human rights. They are protection civilian,violence against women, peace and reconciliation (transitional justice and impunity), and detention. The datas were collected from many sources like books, journals, and websites that can support this research. In this research, the reseacher uses pluralism perspective to describe the role of UNAMA in Afghanistan. This research is supported by international organization theories. Humanitarian assistance concept is also provided to support this research.Keywords : UNAMA, Taliban, conflict, human rights, international organization humanitarian assistance.